Urgensi Transformasi Media Bisnis Di Era Pandemi COVID-19 - Syfa Khoerunisa (Jayapangus Press, 2022)
This study aims to analyze the transformation of business owners from conventional methods to digital platforms to maintain their business in the era of the covid-19 pandemic. This study was conducted using a qualitative method with a phenomenological approach and data collection methods were carried out using a documentation approach from several relevant institutions or previous research. Several policies have been implemented by the government to suppress the spread of the corona virus or covid-19, including PSBB or large-scale social restrictions. The policies implemented have a serious impact on business people in Indonesia. These business people change their business style and communicate with customers, one of which is in marketing and offering types of products to the wider community. Most of the business actors currently choose to use social media and online store applications that are more accessible to all circles of society. Several social networks and online store applications that are widely used by business actors include Facebook, Instagram, TikTok, Shopee, Zalora, Tokopedia, Lazada, and so on.